The whisper man [compact disc, unabridged] - North, Alex (Macmillan Audio, 2019)
After the sudden death of his wife, Tom Kennedy believes a fresh start will help him and his young son Jake heal. A new beginning, a new house, a new town. Featherbank. But the town has a dark past. Twenty years ago, a serial killer abducted and murdered five residents. Until Frank Carter was finally caught, he was nicknamed "The Whisper Man," for he would lure his victims out by whispering at their windows at night.